2023
DOI: 10.3390/su15043531
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sustainability Reporting and Governance in Achieving Sustainable Development Goals: An International Investigation

Abstract: This article explores the role of sustainability reporting and governance in achieving national sustainable development goals. Sustainable development goals focus on economic, societal, and environmental issues and have been set up to address issues regarding environmental degradation, global imbalances, economic instability, social instability, and political instability. Using data from 42 countries over six years, the authors apply panel regression techniques and find a positive relationship between national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 99 publications
(174 reference statements)
0
20
0
2
Order By: Relevance
“…, 2011; Memili et al ., 2017). Previous studies showed that there is a need for good family governance structure to promote the survival of family SMEs (Tadu and Chiguvi, 2019; Al Rawaf and Alfalih, 2023). Our findings are relevant for both Tunisian practitioners and policy-makers to improve the governance practices of family SMEs in order to enhance their sustainable longevity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2011; Memili et al ., 2017). Previous studies showed that there is a need for good family governance structure to promote the survival of family SMEs (Tadu and Chiguvi, 2019; Al Rawaf and Alfalih, 2023). Our findings are relevant for both Tunisian practitioners and policy-makers to improve the governance practices of family SMEs in order to enhance their sustainable longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the study's findings advance the knowledge on the internal determinants of sustainable longevity of family SMEs in developing economies. Thirdly, Governance practices researches are increasingly needed for emerging countries and in different settings (Al Rawaf and Alfalih, 2023), including Tunisia due to its distinctive economic context where the majority of firms are family-owned (Mani and Lakhal, 2015). Thus, this context sheds new light on the characteristics of governance in an emerging country and contributes to the literature of family SMEs by validating the measurement scales of the variables studied in a different context.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, complexities, limitations, and contradictions have become evident, with consequent difficulties in achieving the 17 SDGs [12,13]. In an attempt to ensure that the SDGs are moving in the right direction, it is essential to monitor their progress, assess what has changed since the launch of the SDGs (i.e., evolution since their implementation), detect problems, and define development priorities to be implemented in different contexts [7,9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the results can fuel the discussion and contribute to thinking about the future sustainability framework or strategy to be implemented until 2030, when the SDGs expire, most likely leaving much work to be done. Therefore, monitoring can be fundamental at the local and global policy levels in defining an approach that is more appropriate and realistic [12,13]. The UN encourages specific studies by countries, to accurately assess the SDGs' progress and promote integrated global, national, and regional assessments [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation